Design and analysis of surcharge inlet structure of low flow bypass in detention basin [electronic resource] - 278715 Nor Apaziah Nor Ozman; Fakulti Kejuruteraan Awam (2008)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Hidraul and Hidrologi)) - Universiti Teknologi Malaysia, 2008